AB0553 High cardiovascular risk is related to inflammatory syndrome in patients with ankylosing spondylitis. (23rd January 2014) - Danciu, O. C.; Saulescu, I.; Ionescu, R.
Abstract : Background: Recent studies have suggested that cardiovascular risk in patients with Ankylosing Spondylitis is higher than the one in the general population1 . Uncontrolled inflammatory syndrome might play a significant role, especially in the early stages of cardiovascular injury, determining an earlier onset of atherosclerosis in these patients. Objectives: This cross-sectional study investigates the relationship between inflammatory syndrome and other important variables, such as presence of HLA B27, history of family cardiovascular events, smoking, alcoholism and so on. These and many other variables were also taken into consideration when assessing Patient's cardiovascular risk. Methods: All patients diagnosed with Ankylosing Spondylitis (ASAS Criteria-2011) admitted in Department No X of Hospital "Sfanta Maria", Bucharest, Romania in a two year period were asked to participate in the study. Patients who gave consent (119 patients) were evaluated in regard to inflammatory syndrome using the values for CRP, ESR and fibrinogen. A simplified version of "Framingham Cardiac Risk Score" called "Risk Assessment Tool for Estimating Your 10-year Risk of Having a Heart Attack" was used for predicting the risk for cardiovascular events in 10 years. BASDAI (Bath Ankylosing Spondylitis Disease Activity Index) and BASFI (Bath Ankylosing Spondylitis Functional Index), as well as admission charts and interview were used for obtaining information for other important variables. Results: We found a significant association between higher scores in BASDAI and BASFI and cardiovascular risk (p=0, 01), as well as between higher levels in CRP and cardiovascular risk (p=0, 0001). Body mass index (p=0, 03) and lack of therapy with TNF alfa inhibitors (p=0, 03) also had a negative impact on cardiovascular risk. As regards the inflammatory syndrome, we found that it is significantly associated with higher scores in BASDAI (p=0, 03), lack of therapy with TNF alfa inhibitors (p=0, 01) the presence of HLA B27 (p=0 04) and both axial and peripheral joint impairment (p=0, 04). Conclusions: What is interesting and needs to be mentioned is the significant association between higher levels in CRP and cardiovascular risk but not between ESR or fibrinogen and cardiovascular risk, demonstrating once again that only CRP is a reliable marker for cardiovascular risk. Cardiovascular risk was associated with higher scores in both BASFI and BASDAI tests, but only BASDAI score was associated with inflammatory syndrome. We might advance the premise that when taking into consideration cardiovascular risk, the disease activity- reflected by the scores in BASDAI test- is more important than the disability produced to the patient by this illness. Therapy with TNF alfa inhibitors had a positive influence on both inflammatory syndrome and cardiovascular risk. It is vital to be able to evaluate these patients in regard to cardiovascular impairment, and perhaps cardiac sonography could be considered as a regular step in the initial evaluation for patients with Ankylosing Spondylitis. References: Peters MJ, van der Horst-Bruinsma IE, Dijkmans BA, et al. Cardiovascular risk profile of patients with spondylarthropathies, particularly ankylosing spondylitis and psoriatic arthritis. Semin Arthritis Rheum 2004; 4:585-92. Disclosure of Interest: None Declared